Acute nicotine improves social decision-making in non-smoking but not in smoking schizophrenia patients - Quisenaerts, Charel; Morrens, Manuel; Hulstijn, Wouter; Timmers, Maarten; de Boer, Peter; Sabbe, Bernard; De Bruijn, Ellen R. (Frontiers in Neuroscience, 2013)
Schizophrenia patients are characterized by severe social impairments. Recently, social cognition has been put forward as an important mediator in schizophrenia between the often-reported neurocognitive deficits and functional outcome and is thus an important target for treatments. Nicotine has been reported to improve neurocognitive processes in schizophrenia patients but no studies have investigated possible nicotine-induced facilitation of social cognition. The current placebo-controlled crossover study aimed at bridging this gap by investigating whether the administration of active (1 mg or 2 mg) or placebo oromucosal nicotine spray resulted in improved social decision-making in non-smoking (N=15) and smoking (N=16) schizophrenia patients. All patients played the role of responder in a variant of the ultimatum game that allowed detailed measurements of fairness and intentionality considerations. The results showed impaired social decision-making in the non-smoking patients under placebo, but not in the smoking patients. Interestingly, this impairment normalized after administration of 1 mg of nicotine, but not after 2 mg of nicotine. Nicotine had no effect on performance in the smoking patients. The present study indicates that nicotine improves social decision-making in non-smoking patients. The present results suggest that acute nicotine effects may result in a facilitation of proactive control through improved attentional processes. However, the efficacy seems limited and although nicotine may thus be an interesting target for (social)cognitive enhancement in the subset of patients that do not smoke, more research is needed on the long-lasting effects of nicotine-based treatments.